Generative propagation of Robinia x ambigua POIR. – Pink locust - Rédei, K.; Keserű, Zs.; Osváth-Bujtás, Z.; Malvolti, M. E. (International Journal of Horticultural Science, 2010)
The genus Robinia is a small group of about 10 species of trees and shrubs indigenous only to NorthAmerica. Two species are endemic to Mexico, one being confined to south-western part of the country, while the rest are endemic to the south-eastern part of USA. Of the most important species and varieties of genus Robinia, Robinia x ambigua Poir.(Robinia viscosa x R. pseudo-acacia)-pink locust can be considered as the most significant one for bee-forage and decorative planting. In this paper a generative propagation method is presented for pink locust.